Comparison of Halal Product Assurance System Criteria Arrangement in Indonesia and Malaysia - Sariah SARIAH; Thohir LUTH; Sukarmi SUKARMI; Siti HAMIDAH (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to compare the halal product assurance system regulation that applies in two countries, Indonesia and Malaysia. The halal product assurance system in Indonesia has been regulated through Law no. 33/2014 in conjunction with Law no. 11/2020, Government Regulation No. 39/2021 and Decree of the Head of BPJPH No. 57/2021. Meanwhile, Malaysia's halal product assurance system is regulated in the 2011 PPE, Halal Takrif, procedure manual (MPPHM 2020) and Malaysian Halal Management System (MHMS 2020). This qualitative study uses legal research methods based on the statutory and comparative approaches, which are analyzed prescriptively to find novelty in the form of similarities and differences in the regulation of the halal product assurance system that applies in Indonesia and Malaysia. The similarity is that halal certificates are entirely the state's authority, andhalal standards refer to Islamic law. The difference is that for now, Indonesia refers to HAS 23000 and the Decision of the Head of the Halal Product Assurance Agency (Kepkaban) No. 57/2021, the principle of traceability is not explicitly stated in Kepkaban Np. 57/2021. Malaysia refers to MHMS 2020. The principle of traceability is strictly included in the HAS, and "SERTU" is only intended for large and simple industries.